Pengaruh Pelatihan Kerja dan Teamwork terhadap Kinerja Karyawan pada PDAM Kabupaten Lima Puluh Kota Provinsi Sumatera Barat - Sehani, Sehani; Bagasta, Muhamad; Emti, Desvi (Policy, Law and Political Research Center, 2024)
Employee performance is how someone does the work and the results achieved. These results are employee performance which can be used to determine what level of performance employees are included in the company. The purpose of this study was to pay attention to the effect of job training and teamwork on the performance of PDAM employees, Fifty Cities District, West Sumatra Province. The population in this study were 41 respondents using the saturated sample technique method. Based on the results of this study, it shows that job training partially has a significant and positive effect on the performance of PDAM employees in Fifty Cities Regency, West Sumatra Province. Teamwork partially has a significant and positive effect on the performance of PDAM employees in the Fifty Cities district of West Sumatra Province. The results of the coefficient of determination show that the magnitude of the influence of the two independent variables together on the dependent variable is 58%, and the remaining 42% is another variable not examined in this study.